Ybor City : crucible of the Latina South - McNamara, Sarah, 1987- (Chapel Hill : The University of North Carolina Press, 2023)
"When we think about the origins of Cuban immigration to the United States, we often imagine the anti-Communist exiles who fled the regime of Fidel Castro and settled in South Florida during the 1950s and 1960s. But before Miami became Havana USA, a wave of leftist, working-class migrants from prerevolutionary Cuba crossed the Florida Straits and made Ybor City the center of the immigrant South and the global capital of the Cuban cigar industry. Located on the eastern edge of Tampa, a port city along Florida's Gulf Coast, Ybor was a multiracial, multiethnic neighborhood where radical thinkers and laborers found work and refuge against the shifting tides of international political turmoil during the early half of the twentieth century. In this book, Sarah McNamara tells the story of how immigrant women ensured and fought for community survival across generations and against the backdrop of a post-Confederate, Jim Crow-controlled southern order"--Provided by publisher.
Chapter One: Building -- Chapter Two: Resisting -- Chapter Three: Surviving -- Chapter Four: Remaking.
Includes bibliographical references and index.
Description based upon print version of record.
JSTOR
Keywords: Immigrants -- Political activity -- Florida -- Tampa; Cubans -- Political activity -- Florida -- Tampa; Anti-fascist movements -- Florida -- Tampa; Women cigar makers -- Political activity -- Florida -- Tampa; Cuban Americans -- Florida -- Tampa -- Social conditions; Cuban American women -- Florida -- Tampa -- History; Cubans -- Florida -- Tampa -- History; Cuba -- History -- Autonomy and independence movements; Ybor City (Tampa, Fla.) -- Race relations -- History; Ybor City (Tampa, Fla.) -- History; Ethnic attitudes -- Florida -- Tampa -- History; Cigar industry -- Florida -- Tampa -- History; Immigrants -- Florida -- Tampa -- History; History; Minorities -- Study and teaching; Social sciences; Electronic books; Cubains -- Activité politique -- Floride -- Tampa; Antifascisme -- Floride -- Tampa; Cigarières -- Activité politique -- Floride -- Tampa; Américains d'origine cubaine -- Floride -- Tampa -- Conditions sociales; Américaines d'origine cubaine -- Floride -- Tampa -- Histoire; Cubains -- Floride -- Tampa -- Histoire; Cuba -- Histoire -- Autonomie et mouvements indépendantistes.; Attitudes ethniques -- Floride -- Tampa -- Histoire; Cigares -- Industrie -- Floride -- Tampa -- Histoire; Histoire; Minorités -- Étude et enseignement; Sciences sociales; Livres numériques.; history (discipline); ethnic studies; social sciences; e-books.; 20th Century; United States; HISTORY; Women's Studies; SOCIAL SCIENCE; Immigrants; Ethnic attitudes; Cigar industry; Anti-fascist movements; Autonomy and independence movements; Cuban American women; Cuban Americans -- Social conditions; Cubans; Cubans -- Political activity; Immigrants -- Political activity; Race relations; Cuba; Florida -- Tampa; Florida -- Tampa -- Ybor City; History of the Americas; History; Electronic books; History